Introduction to nanoscience - Hornyak, Gabor L. (Gabor Louis); Dutta, Joydeep; Rao, Anil; Tibbals, H.F.; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2008)
Tomorrow's nanoscientist will have a truly interdisciplinary and nano-centric education, rather than, for example, a degree in chemistry with a specialization in nanoscience. For this to happen, the field needs a truly focused and dedicated textbook. This full-color masterwork is such a textbook. It introduces the nanoscale along with the societal impacts of nanoscience, then presents an overview of characterization and fabrication methods. The authors systematically discuss the chemistry, physics, and biology aspects of nanoscience, providing a complete picture of the challenges, opportunities, and inspirations posed by each facet before giving a brief glimpse at nanoscience in action: nanotechnology.
part Section 1: Perspectives -- chapter 1 INTRODUCTION -- chapter 2 SOCIETAL IMPLICATIONS OF NANO -- part Section 2: Nanotools -- chapter 3 CHARACTERIZATION METHODS -- chapter 4 FABRICATION METHODS -- part Section 3: Physics: Properties and Phenomena -- chapter 5 MATERIALS, STRUCTURE, AND THE NANOSURFACE -- chapter 6 ENERGY AT THE NANOSCALE -- chapter 7 THE MATERIAL CONTINUUM -- chapter 8 NANOTHERMODYNAMICS -- part Section 4: Chemistry: Synthesis and Modification -- chapter 9 CARBON-BASED NANOMATERIALS -- chapter 10 CHEMICAL INTERACTIONS AT THE NANOSCALE -- chapter 11 SUPRAMOLECULAR CHEMISTRY -- chapter 12 CHEMICAL SYNTHESIS AND MODIFICATION OF NANOMATERIALS -- part Section 5: Natural and Bionanoscience -- chapter 13 NATURAL NANOMATERIALS -- chapter 14 BIOMOLECULAR NANOSCIENCE.
Keywords: Nanoscience; Nanostructured materials; Nanostructures; Nanotechnology; SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; TECHNOLOGY & ENGINEERING / Textiles & Polymers